2005
DOI: 10.1016/j.febslet.2005.07.065
|View full text |Cite
|
Sign up to set email alerts
|

Exclusive paternal expression and novel alternatively spliced variants of ε‐sarcoglycan mRNA in mouse brain

Abstract: Mutations of SGCE encoding e-sarcoglycan cause myoclonus-dystonia. SGCE is paternally expressed; however, 5-10% of patients show maternal inheritance of the disease. We found Sgce was exclusively paternally expressed in mice by using a novel polymorphism marker. The result was confirmed in Sgce heterozygous knockout mice. This finding suggests that maternally inherited myoclonus-dystonia may not result from maternal expression of SGCE. Furthermore, we report a new family of alternatively spliced Sgce mRNA expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
44
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 36 publications
2
44
0
1
Order By: Relevance
“…In this study, we show that the SGCE imprinting pattern is retained in different human brain regions and different human tissues (muscle, blood) similar to what has been shown in mice. 18 Thus, the brain-specific M-D phenotype cannot be explained by a brain region-or tissue-specific imprinting. As not all M-D patients have mutations in SGCE, silencing of SGCE expression owing to imprinting defects could also be a possible disease mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we show that the SGCE imprinting pattern is retained in different human brain regions and different human tissues (muscle, blood) similar to what has been shown in mice. 18 Thus, the brain-specific M-D phenotype cannot be explained by a brain region-or tissue-specific imprinting. As not all M-D patients have mutations in SGCE, silencing of SGCE expression owing to imprinting defects could also be a possible disease mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Monoallelic paternal SGCE expression has been shown in human blood leukocytes and in human and mice brain. 15,18 Several genes are known to show tissue-specific imprinting 22 and brain cell-type-or region-specific imprinting. 23 The latter has not yet been investigated for SGCE, but is important to address, as only regions in which the imprint is maintained can be involved in the M-D pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The protein sequence homology analysis and 3D structure modeling suggest that "-sarcoglycans has a cadherin-like domain at the N-terminal extracellular region, suggesting it may function in intercellular adhesion (26). Mouse "-sarcoglycan has alternative splicing variants and the brain-specific isoforms have PDZ-binding motifs (27). Mouse "-sarcoglycan is enriched in pre-and post-synaptic membrane fractions, suggesting a role in synaptic transmission (28).…”
mentioning
confidence: 99%
“…Mouse "-sarcoglycan is enriched in pre-and post-synaptic membrane fractions, suggesting a role in synaptic transmission (28). Sgce is maternally imprinted and paternally expressed in humans and rodents (27,29,30). We previously reported the making of Sgce KO mice lacking exon 4 and demonstrated that paternally inherited Sgce heterozygous KO mice did not express maternally inherited WT Sgce in the brain (27).…”
mentioning
confidence: 99%